Lupus patient decisions about clinical trial participation: a qualitative evaluation of perceptions, facilitators and barriers. Issue 1 (15th March 2020) - Arriens, Cristina; Aberle, Teresa; Carthen, Fredonna; Kamp, Stan; Thanou, Aikaterini; Chakravarty, Eliza; James, Judith A; Merrill, Joan T; Ogunsanya, Motolani E
Abstract : Objective: Although SLE disproportionately affects minority racial groups, they are significantly under-represented in clinical trials in the USA. This may lead to misleading conclusions in race-based subgroup analyses. We conducted focus groups to evaluate the perceptions of diverse patients with lupus about clinical trial participation. Methods: A qualitative research design employed three 90 min focus groups led by a trained moderator and guided by the Theory of Planned Behaviour. Open-ended questions about trial participation included advantages and disadvantages (behavioural beliefs), approving and disapproving significant others (normative beliefs), and participation enhancers and barriers (control beliefs). Discussions were recorded, transcribed and analysed to identify emerging themes. Results: Patients with SLE (n=23) aged 21–72, with increased proportion of minority groups (65%), participated. Reported advantages of trial participation included altruism and personal benefit. Disadvantages included uncertainties, disappointment, information burden, and life–health balance. Although some patients had discussed research participation with approving or disapproving family or friends, self-approval superseded external approval. Barriers included logistics and time, and facilitators included flexibility in scheduling, advance notice of studies, streamlined forms, and hope for SLE improvement. Conclusions: Knowledge about potential benefits of clinical trial participation was high. Minority patients demonstrated confidence in making their own informed decisions, but major barriers for all participants included burdensome forms, travel, childcare, and work. These suggest a major impact on minority and all recruitment from behavioural and control aspects, which should be considered in the logistics of trial design. This does not minimise the potential importance of improved access and education about clinical research.